Tc Saturation and Possible Electronic Phase Separation in Strongly Overdoped Cuprates - Amirreza Hemmatzade; Elena Medina; Ludovic Delbes; Benoît Baptiste; David Hrabovsky; Yannick Klein; Steven D. Conradson; Maarit Karppinen; Andrea Gauzzi (Condensed Matter, 2023)
In order to elucidate the unusual superconducting properties of cuprates in the strongly overdoped region, i.e., at hole-doping levels <semantics>p≳0.4</semantics>/Cu in the CuO<semantics>2</semantics> plane, we study the structural and superconducting properties of a series of Cu<semantics>0.75</semantics>Mo<semantics>0.25</semantics>Sr<semantics>2</semantics>YCu<semantics>2</semantics>O<semantics>7+x</semantics> powder samples oxygenated under high pressure using different concentrations of KClO<semantics>3</semantics> up to 35 mol %. The analysis of X-ray diffraction data indicates a high purity ∼90% of all samples and suggests that the concentration, x, of extra oxygen atoms increases with increasing KClO<semantics>3</semantics> concentration. Surprisingly, the <semantics>Tc</semantics> values remain nearly constant within the 80–85 K range independent of KClO<semantics>3</semantics> concentration, which suggests a scenario of <semantics>Tc</semantics> saturation. In order to account for this unexpected behaviour, we put forward the hypothesis that overdoping enhances the density of unpaired holes, which is supported by the observation of large values of the Sommerfeld coefficient in all samples. We therefore propose a scenario of electronic phase separation between normal and superconducting holes.